2011
DOI: 10.1177/0954407011406469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a split-injection strategy on the performance of stratified lean combustion for a gasoline direct-injection engine

Abstract: Fuel economy can be significantly improved in a gasoline direct-injection (GDI) engine owing to the stratified mixture formation strategy which guarantees stable combustion under ultra-lean air–fuel mixture conditions. In the GDI engine, it is widely accepted that the spray-guided direct-injection system, which is characterized by a close configuration between the centrally mounted injector and the spark plug, is regarded as a promising technology among the efforts to realize stratified lean combustion. With t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The formation of an overly lean mixture can be another reason for increased THC emissions. The CO emission behavior is very similar to that of THC emissions, and is consistent with the results of previous studies on lean mixture combustion [6,7,16,17,20,22,30]. …”
Section: Effect Of Fuel Injection Ratio On Engine Emissionssupporting
confidence: 90%
See 1 more Smart Citation
“…The formation of an overly lean mixture can be another reason for increased THC emissions. The CO emission behavior is very similar to that of THC emissions, and is consistent with the results of previous studies on lean mixture combustion [6,7,16,17,20,22,30]. …”
Section: Effect Of Fuel Injection Ratio On Engine Emissionssupporting
confidence: 90%
“…However, the optimal fuel injection, spark ignition timing, and ratio of injected fuel amount can differ according to the operating point. As the formation of an appropriate stratified mixture is difficult with a single injection at a certain operating condition, multiple injection strategies were employed in the previous studies [7,16,17,22,25]. In the present study, a two-staged injection strategy is applied and optimized.…”
Section: Introductionmentioning
confidence: 99%
“…However, because of mixture scavenging, which leads to fuel short-circuiting and excessive exhaust emissions, 1 people are trying to replace the conventional fuel injection system with gasoline direct injection (GDI) to reduce fuel consumption and CO 2 emission and to improve engine power output. 2 The GDI fuel injection system sprays fuel directly into the combustion chamber with a high injection pressure, resulting in a good atomization and evaporation process, 3,4 which have been widely used in automobiles. However, the normal GDI system has a complex structure which is not good for an aviation piston engine.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results from a spray-guided SIDI engine under lean combustion concluded that double injection strategy provides the potential to increase combustion efficiency, to improve combustion stability, and to reduce NO x (oxides of nitrogen) emission as compared to single injection strategy. 17 Park et al 18 indicated that the excess air ratio is one of the important factors affecting the thermal efficiency and nitrogen oxide (NO x ) emission, and it is significantly extended to λ = 2.0 by the split-injection scheme. Two fuel injection strategy with a short delay is a very effective method to ensure combustion stability under lean operation conditions, but it causes a lack of time for fuel evaporation which generates smoke emission.…”
Section: Introductionmentioning
confidence: 99%